Implementation of Choosing Wisely in gynecology and obstetrics internship - Dilton Rodrigues Mendonça; Milena Bastos Brito; Carolina Villa Nova Aguiar; Liliane Lins-Kusterer; Ana Carolina Fonseca Scavuzzi; Marta Silva Menezes (Escola Bahiana de Medicina e Saúde Pública, 2024)
INTRODUCTION: Throughout undergraduate school, it is important to instill a continuous emphasis on cost-conscious thinking across all specialties, including obstetrics and gynecology (OB/GYN). One potential strategy is the implementation of the Choosing Wisely (CW) Campaign. OBJECTIVE: To describe and assess the implementation strategies of the Choosing Wisely (CW) campaign within a medical internship in Obstetrics and Gynecology (OB/GYN). METHODS: This intervention study involved medical teachers and undergraduate medical students at a Brazilian medical school. Initially, teachers identified three common unnecessary clinical scenarios, which were then grouped and adapted to fit the CW recommendation format. Based on the five most frequently occurring recommendations, educational activities were developed, including workshops, banners, and discussions on cost-consciousness in healthcare with undergraduate students and medical doctors. RESULTS: The top five recommendations were as follows: 1. Don't routinely order hormone levels for menopause diagnosis; 2. Don't recommend ovarian removal during hysterectomy for premenopausal women without ovarian câncer risk; 3. Don't prescribe broad-spectrum antibiotics for uncomplicated acute cystitis treatment; 4. Don't request preventive examinations for colpitis diagnosis; and 5. Don't request unnecessary exams during low-risk prenatal care, such as kidney and liver function tests. The theoretical and practical components of these educational activities led to increased awareness and subsequent discussions among internship faculty and undergraduate students. CONCLUSION: Implementation of the CW campaign within the medical internship in OB/GYN resulted in a positive impact, fostering reflection among participants and aiding in the avoidance of unnecessary treatments or prescriptions.